The Role of Social Ties in Factor Allocation - Beck, Ulrik; Bjerge, Benedikte; Fafchamps, Marcel (World Bank, Washington, DC, 2018)
This paper investigates whether social structure helps or hinders factor allocation using unusually rich data from The Gambia. Evidence indicates that land available for cultivation is allocated unequally across households; and that factor transfers are more common between neighbors, co-ethnics, and kinship related households. Does this lead to the conclusion that land inequality is due to flows of land between households being impeded by social divisions? To answer this question, a novel methodology that approaches exhaustive data on dyadic flows from an aggregate point of view is introduced. Land transfers lead to a more equal distribution of land and to more comparable factor ratios across households in general. But equalizing transfers of land are not more likely within ethnic or kinship groups. In conclusion, ethnic and kinship divisions do not hinder land and labor transfers in a way that contributes to aggregate factor inequality. Labor transfers do not equilibrate factor ratios across households. But it cannot be ruled out that they serve a beneficial role, e.g., to deal with unanticipated health shocks.